2009
DOI: 10.5194/cp-5-53-2009
|View full text |Cite
|
Sign up to set email alerts
|

Millennial-scale climatic variability between 340 000 and 270 000 years ago in SW Europe: evidence from a NW Iberian margin pollen sequence

Abstract: Abstract.We present a new high-resolution marine pollen record from NW Iberian margin sediments (core MD03-2697) covering the interval between 340 000 and 270 000 years ago, a time period centred on Marine Isotope Stage (MIS) 9 and characterized by particular baseline climate states. This study enables the documentation of vegetation changes in the north-western Iberian Peninsula and therefore the terrestrial climatic variability at orbital and in particular at millennial scales during MIS 9, directly on a mar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 82 publications
(179 reference statements)
4
13
0
1
Order By: Relevance
“…It is likely that the low gradient of the terraces (0.003 to 0.007 m km − 1 ) in combination with high infiltration capacity of the terraces, prevented overland flow. Additional factors may be that the underlying granites weathered rapidly, thus preventing water stagnation, also that the Miño catchment has always been vegetated, even during the coldest spells of the glacial periods (Sanchez-Goñi et al, 2008;Desprat et al, 2009). It has also been demonstrated that fluvial systems with moderate vertical uplift rates (typically 0.08 to 0.11 m ka − 1 ) have the largest potential for alluvial terrace preservation (Veldkamp and Van den Berg, 1993).…”
Section: Miño Terrace Denudation Ratesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is likely that the low gradient of the terraces (0.003 to 0.007 m km − 1 ) in combination with high infiltration capacity of the terraces, prevented overland flow. Additional factors may be that the underlying granites weathered rapidly, thus preventing water stagnation, also that the Miño catchment has always been vegetated, even during the coldest spells of the glacial periods (Sanchez-Goñi et al, 2008;Desprat et al, 2009). It has also been demonstrated that fluvial systems with moderate vertical uplift rates (typically 0.08 to 0.11 m ka − 1 ) have the largest potential for alluvial terrace preservation (Veldkamp and Van den Berg, 1993).…”
Section: Miño Terrace Denudation Ratesmentioning
confidence: 96%
“…Vandenberghe, 1995;Busschers et al, 2007;Bridgland and Westaway, 2008). The greater part of the catchment was always vegetated and relatively humid (Desprat et al, , 2009 (Lisiecki and Raymo, 2005). The Y-axis is inverted.…”
Section: Driving Forces Behind Terrace Formationmentioning
confidence: 97%
“…BP) The relevant presence of Fagus pollen offshore the Iberian margin is basically focussed on the isotopic interglacials MIS 11 and MIS 9 (Desprat et al 2005(Desprat et al , 2008 although only a few grains appeared belonging to MIS-5 or younger . The local presence of F. sylvatica woodlands in NW Iberia during the final stages of the Pleistocene has recently been inferred by pollen analysis of ancient limnetic levels (Gómez-Orellana 2002;Gómez-Orellana et al 2007).…”
Section: Spatial Analyses Of the F Sylvatica L Distribution In Nw Imentioning
confidence: 99%
“…well into the interglacial setting MIS 9e apart from other interglacial intervals. This difference is not only evidenced by the prolonged planktic δ 13 C minimum but also by the persistent, if low presence of the polar species N. pachyderma (s) in the planktic foraminifer fauna off Iberia during the first half of the interglacial (de Abreu et al, 2005;Desprat et al, 2009) implying the advection of poorly ventilated waters into the mid-latitude North Atlantic. These waters were most likely Subarctic Intermediate Water because the record of ODP Site 982 on the northern Reykjanes ridge (57.5 • N) reveals the same δ 13 C minimum accompanied by persistent, but low input of IRD (Venz et al, 1999).…”
Section: Basinwide Circulation and Linkages To Thermocline Water Sourcesmentioning
confidence: 99%